Treadmill exercise improves short-term memory by enhancing neurogenesis in amyloid beta-induced Alzheimer disease rats - Kim, Bo-Kyun; Shin, Mal-Soon; Kim, Chang-Ju; Baek, Sang-Bin; Ko, Yeong-Chan; Kim, Young-Pyo (Journal of exercise rehabilitation, 2014)
Alzheimer’s disease is one of the most devastating neurodegenerative disorders, and this disease is characterized by severe memory impair-ment and decline of cognition. Hippocampal neurons are vulnerable to injury induced by Alzheimer’s disease. Physical exercise is known to promote cell survival and functional recovery after brain injuries. In the present study, we investigated the effects of treadmill exercise on short-term memory in relation with neurogenesis in the rats with amyloid β25-35 (Aβ25-35)-induced Alzheimer’s disease. The rat model of Alzheimer’s dis-ease was induced by the intracerebroventricular (ICV) injection of Aβ25-35, using a stereotaxic instrument. The rats in the exercise group were forced to run on a treadmill for 30 min once daily for 4 consecutive weeks, starting 2 days after Aβ25-35 injection. Presently, short-term memory was deteriorated and apical dendritic length in the hippocampus was short-ened in the hippocampus by Aβ25-35 injection. In contrast, treadmill exer-cise alleviated memory impairment and increased apical dendritic length in the Aβ25-35-injected rats. Neurogenesis and brain-derived neurotor-phic factor (BDNF) and tyrosine kinase B (trkB) in the hippocampal den-tate gyrus were decreased by Aβ25-35 injection. Treadmill exercise in-creased neurogenesis and expressions of BDNF and trkB expressions. The present study shows that treadmill exercise may provide therapeu-tic value for the alleviating symptoms of Alzheimer’s disease.